Peran Orang Tua Dalam Mendorong Pendidikan Anak Di Dusun Pemuteran Desa Pempatan Karangasem - Safitri, Leni; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT The role of parents in encouraging children’s education in Dusun Pemuteran, Desa Pempatan, Karangasem is still relatively low and not a few parents have self-gap. Parental self-gap in the study area is not determined by symbolic and ideal images but is rather the construction of each parent. It is said that because many parents in the area have arguments such as, “why pursue higher education when ultimately work as farmers, market labors, and various other types of work that rely on physical strength”. In this case, parents should give their best role to their children so parents must carry out roles that are able to encourage children toward success. Keywords: Role Of Parents, Children Education, Drop Out Of School